Strategi Bisnis Showroom Penjualan Motor Bekas Ditinjau dari Analisis Pendapatan: (Studi di Kuala Tungkal Kabupaten Tanjung Jabung Barat) - Eni Wahyuni; Nurlia Fusfita; Sri Rahma (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to identify the business strategies implemented by used motorcycle showrooms and to examine their impact on the income generated. The research focuses on four used motorcycle showrooms located on Jalan Panglima, Kuala Tungkal, Tanjung Jabung Barat Regency. The intense competition in a concentrated area encourages each showroom to adopt appropriate strategies to remain competitive and sustain stable income. This research uses a qualitative approach with a comparative study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that each showroom implements different business strategies based on their internal strengths and market characteristics. Showrooms that combine the marketing mix (7P) with good service approaches tend to earn higher income. Additionally, Islamic business values such as honesty, transparency, and trustworthy service contribute to the effectiveness of the strategies applied.